Muhammadiyah And Aisyiyah Involvement In Public Policy Making In Ponorogo District - Sulton, Sulton; Mahardhani, Ardhana Januar; Sunarto, Sunarto (UNIVERSITAS PAKUAN, 2023)
This paper will provide a description of the involvement of Muhammadiyah and Aisyiyah in making a public policy made by the Regional Government of Ponorogo Regency. The focus of the research is how the pattern of organizational involvement through four indicators, namely 1) Participation in decision making, 2) Participation in implementation, 3) Participation in making use of, and 4) Participation in evaluation. This study uses a qualitative method with research informants namely Muhammadiyah Regional Leaders represented by the Economic Council, Aisyiah Regional Leaders, and representatives from an autonomous organization, namely the Muhammadiyah Student Association. Collecting data using observation, structured interviews, and documentation. The results obtained from this study are that the three units in the Muhammadiyah Regional Leadership and Aisyiyah Regional Leadership play an active role and always follow developments in Ponorogo Regency, besides that the Ponorogo Regency Government itself also always involves the two organizations in accordance with the policies set forth being prepared by the regional government starting from decision making, implementation, utilization, and evaluation